Nomenclatural notes on Behuria (Melastomataceae - Merianieae) - Baumgratz,José Fernando A. (2010)
Abstract This study adds new synonyms, combinations, and lectotypifications for the genus Behuria. Three synonyms are proposed, Benevidesia (= Behuria), Behuria corymbosa var. grandifolia (= Behuria corymbosa) and Behuria souzalimae var. pallescens (= Behuria souzalimae), two new combinations, Behuria organensis (= Benevidesia organensis) and Behuria magdalenensis (= Benevidesia magdalenensis), and ten lectotypifications as follows: B. cordifolia, B. corymbosa, B. corymbosa var. grandifolia, B. glazioviana, B. glutinosa , B. insignis, B. magdalenensis , B. mouraei , B. organensis, and B. parvifolia.